Realistic mathematic education (RME) sebagai model pembelajaran - Badriyah, Lailatul (Maliki Interdisciplinary Journal, 2025)
In the 21st century, students are required to have critical, creative, communicative, and collaborative thinking skills, one of which is in mathematics. However, in reality, mathematics learning in schools is often still conventional, resulting in students having difficulty in understanding concepts in depth. One way to overcome this is to select an appropriate learning model, one that can be used is the Realistic Mathematical Education model. This article specifically discusses Realistic Mathematical Education as a learning model. The research method used in this article is a literature study of several journal articles related to Realistic Mathematical Education. The results of the study revealed that Realistic Mathematical Education as a learning model has three main principles: Guided Reinvention and Progressive Mathematization, Didactic Phenomenology, and Self-Developed Models. The characteristics of this model are contextual, using models and representations, gradual, interactive, and reflective. The RME model is supported by several learning theories, namely constructivism, Vygotsky, and Bruner. The syntax or learning steps include understanding contextual problems, explaining contextual problems, solving contextual problems, comparing and discussing answers, and concluding.